KECEMASAN ANAK DITINJAU DARI KECEMASAN ORANG TUA DI RSU. BHAKTI HUSADA KRIKILAN: Review Child's Anxiety from Parents' Anxiety in Bhakti Husada Krikilan General Hospital - Eko Prabowo; Lediana Oktaviani (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2021)
Introduction: Illness and hospitalization cause a crisis in children's lives. In the hospital, the child must face an unfamiliar environment. Often they have to undergo procedures that cause pain, loss of independence and various unknowns. Anxiety that occurs in hospitalized children can be caused by separation which is indicated by refusing to eat, crying and being uncooperative with health workers. Loss of control causes children to become irritable and aggressive, loss of self-concept and body image. Objective: The purpose of this study was to determine the anxiety of children in terms of the anxiety of parents in the RSU. Bhakti Husada Krikilan. Methods: This study uses a correlational design with the type of research used is descriptive analytic. The population in this study was the average of pediatric patients and their parents during the last 3 months in the Inpatient Room at the RSU. Bhakti Husada Krikilan as many as 60 people. Sampling technique using simple random. The tool for the data collection process is a questionnaire sheet, which is then analyzed by the Spearman Rank statistic test. The decision was taken by comparing the p value < 0.05. Results: Based on the results of the study showed that from 49 respondents showed that most of the respondents had parental anxiety in the moderate category as many as 33 people (67.3%). While most of the respondents had child anxiety in the severe category as many as 28 people (57.1%). Based on the results of the Spearman Rank test, it is known that there is a relationship between children's anxiety in terms of parental anxiety at the RSU. Bhakti Husada Krikilan Banyuwangi in 2020 because the p value < 0.05, which is 0.25. Conclusion: Parents with excessive anxiety tend to be more afraid of things that are uncertain. This keeps them from paying close attention to what is really going on and what is in front of them. So, this will make parenting not work as it should. This condition also triggers anxiety in children. For this reason, it is necessary to increase assistance to children to provide a sense of security and comfort so that children's anxiety will decrease